Agri reform: From production to profitability - Verma, Smriti (Indian Express Group, 2019)
The idea of doubling farmers’ incomes by 2022, when the country completes 75 years of its independence, was shared by prime minister Narendra Modi at a kisan rally in Bareilly (Uttar Pradesh) in February 2016. The announcement triggered a multitude of committees, panels, and agendas to be set up at various tiers of the government in pursuance of this objective. Despite zealous efforts made by government agencies toward fulfilment of this goal, the state of farmers and agriculture has shown little or no improvement. We must look for new pathways that can leverage India’s advantages of abundance in land, water, fertile soil, cheap labour, and favourable agro-climatic conditions to the benefit of farmers as well as farming. Farmer business school (FBS) is a new idea picking up steam across developing countries for making agriculture a profitable enterprise.